Penggunaan Media Pagarbilang untuk Meningkatkan Hasil Belajar Membandingkan Pecahan Berpenyebut Beda - Istafada Istafada (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The low understanding of mathematical concepts received by students will also result in low student learning outcomes in mathematics. Using the right learning media can help students learn math concepts easily. This study aims to improve student learning outcomes in the matter of comparing fractions with different denominators by using the word media. This study uses action research (action research) as much as two cycles. There are 4 stages of each cycle, namely planning, action, observation, and reflection. The results of this study indicate that the use of Pagarbilang media can improve student learning outcomes in comparing fractions with different denominators, namely an average of 79.42 becomes 85.28 and student mastery increases from 86.11% to 94.44%.